A study on compliance to epileptic drug among epileptic patient attending physician clinic HUSM - Shaaban, Juwita (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Method: This is a cross sectional study involving 297 epilepsy patients attended Neurology Clinic, HUSM from January until November 2008 using self-administered validated questionnaires which consist of compliance, psychosocial evaluation and satisfaction with health care which has I 0, 39 and 23 items respectively. Result: The prevalence of non-compliant to epileptic drugs was 52.2% and the factors that contribute to non-compliant were patients' understanding about their illness (p= 0.002), complexity of the drug regime (p= 0.001) and cost and physical changes of the medication (p=0.004). There were no associations between sociodemographic, patient satisfaction with health care and other psychosocial factors with drug compliance. Conclusion: The drug non compliant is high among epilepsy patients attending Neurology Clinic, HUSM. Factors associated with drug compliance include duration of epilepsy, patient understanding about the illness, complexity of the drug regime and cost and physical of the medication. Assessment of drug compliance should be a routine part in managing epilepsy patients. Recognization of factors that contribute to non compliant will help the health care provider to plan an intervention programme to improve drug compliance and consequently reduces the cost of managing epilepsy patient.